1993
DOI: 10.1029/92tc00598
|View full text |Cite
|
Sign up to set email alerts
|

Lithoprobe crustal reflection structure of the Southern Canadian Cordillera 2: Coast mountains transect

Abstract: The Lithoprobe seismic reflection transect across the southern Coast Mountains of the Canadian Cordillera images fundamental crustal structures presumably related to collision of the Intermontane and Insular composite terranes, and deep levels in the upper plate of the offshore Cascadia subduction belt. The eastern part of the Coast Mountains are characterized by east dipping upper crustal reflectors that project to exposed faults and east dipping lower crustal reflectors; they are truncated by subhorizontal t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0

Year Published

1993
1993
2017
2017

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 62 publications
(29 citation statements)
references
References 53 publications
1
28
0
Order By: Relevance
“…Comparable large-scale antiforms have been identified in a deep seismic profile across the northern part of Stikinia where no major crustal extension is identified (Cook et al 2004). An antiform that flattens with depth, soling into the reflective lower crust, forms the core of the Nicola horst in the southern Canadian Cordillera (Varsek et al 1993), and this geometry is similar to that observed on line 13; however, we do not observe isolated strong reflectors within the lower crust that are as laterally continuous as those seen beneath, and adjacent to, the Nicola horst.…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…Comparable large-scale antiforms have been identified in a deep seismic profile across the northern part of Stikinia where no major crustal extension is identified (Cook et al 2004). An antiform that flattens with depth, soling into the reflective lower crust, forms the core of the Nicola horst in the southern Canadian Cordillera (Varsek et al 1993), and this geometry is similar to that observed on line 13; however, we do not observe isolated strong reflectors within the lower crust that are as laterally continuous as those seen beneath, and adjacent to, the Nicola horst.…”
Section: Discussionsupporting
confidence: 71%
“…The seismic reflection lines of the Southern Cordillera (SC) transect, which were acquired in the late 1980's, were the first seismic transect across the Cordillera, and revealed the complex history of the orogen and its subsequent modification by extension (Cook et al 1992;Varsek et al 1993). The seismic lines of the Slave -Northern Cordillera Lithosphere Evolution (SNORCLE) transect were acquired ϳ10 years later, and, with the further development of seismic acquisition technology during that period, provided significantly improved reflection data from the deeper crust and uppermost mantle (Cook et al 2004;Evanchick et al 2005).…”
Section: Introductionmentioning
confidence: 99%
“…McLean, in preparation), high heat flow (Lewis et al 1988(Lewis et al , 1992, low Bouguer gravity (Riddihough and Seeman 1982), and high electrical conductivity (Gough and Majorowicz 1992;Jones et al 1992). As well, Lithoprobe seismic reflection data show intracrustal reflections which have been interpreted in terms of structural features (Monger and Journeay 1992;Varsek et al 1993); line 10 offers a means of extending these results beyond 2D interpretations. Can.…”
Section: Tectonic Historymentioning
confidence: 94%
“…Seismic reflection data indicate that the Pasayten fault dips eastward, juxtaposing Cretaceous volcano-plutonic rocks of Quesnellia over sedimentary successions of the Methow/ Methow-Tyaughton basin (Figs. 1, 4;Varsek et al, 1993).…”
Section: Structural Settingmentioning
confidence: 99%